Diversity of Family Myrtaceae Juss. 1789 in Ha Tinh Province - Khanh, Tran Hau; Ban, Pham Hong; Hoi, Tran Minh; Ha, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology, 2021)
The study result of Myrtaceae family in Ha Tinh province reported, 61 species of 13 genera.  In of them 36 species and 6 genera have been added to the list of Ha Tinh province (2021). The family myrtaceae in Ha Tinh province has many different uses: 61 species for essential oils, 46 species for timber plants, 30 species for medicinal plants, 24 species for edible, 11 species for ornamental plants, 7 species for different uses and 4 species for tannin plants. In the stems form, the large groups of trees with 10 species, followed by average groups of trees with 15 species; small of trees dominated with 26 species and groups of shrubs 10 species. There are 4 major habitats: forest with 35 species (57.38%), light forest with 35 species (57.38%), subforest with 50 species (81.97%), along streams and beside the road with 35 species (57.38%).